A Bead‐Based Proximity Assay for BRD4 Ligand Discovery. Issue 4 (2nd December 2015) - Roberts, Justin M.; Bradner, James E.
Abstract : Bromodomain‐containing proteins have emerged as desirable targets for anti‐neoplastic and anti‐inflammatory drug discovery. Toward the development of selective inhibitors of the BET family of bromodomains, we optimized bead‐based assays to detect interactions between bromodomains and poly‐acetylated histone peptides. Donor and acceptor beads bound to target and ligand are brought into proximity by this protein‐protein interaction. After laser illumination, singlet oxygen evolved from donor beads travels to the spatially close acceptor beads, resulting in chemiluminesence. This AlphaScreen assay has proven amendable to high‐throughput screening, secondary validation, and specificity profiling during lead discovery and optimization. Here we report our protocol for assay development to measure inhibition of ligand binding to bromodomain‐containing protein 4 (BRD4). We discuss the discovery of an appropriate probe, optimization of bead, probe, and protein concentrations, and the derivation of protein‐probe inhibition curves. Finally, we explore the implementation of this technology for high‐throughput screening of potential BRD4 inhibitors. © 2015 by John Wiley & Sons, Inc.